2016
DOI: 10.1074/jbc.m116.742981
|View full text |Cite
|
Sign up to set email alerts
|

The Stalk Domain of NKp30 Contributes to Ligand Binding and Signaling of a Preassembled NKp30-CD3ζ Complex

Abstract: Edited by Peter CresswellThe natural cytotoxicity receptor (NCR) NKp30 (CD337) is a key player for NK cell immunosurveillance of infections and cancer. The molecular details of ligand recognition and its connection to CD3 signaling remain unsolved. Here, we show that the stalk domain ( 129 KEHPQLGAGTVLLLR 143 ) of NKp30 is very sensitive to sequence alterations, as mutations lead to impaired ligand binding and/or signaling capacity. Surprisingly, the stalk domains of NKp30 and NKp46, another NCR employing CD3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 41 publications
(66 reference statements)
1
14
0
Order By: Relevance
“…Impaired oligomerization would then translate into lower apparent binding affinities, when using surface-based methods such as SPR and ELISA, and into impaired signal transduction in cell-based experiments. The role of the stalk domain in CD3ζ-mediated activation of NK cells was thoroughly characterized by Memmer et al [ 7 ] who showed that mutations in the stalk region close to LBD weaken the K D of B7-H6-Fc whereas BAG-6 binding, again, remained mostly unaffected, although NKp30-Fc IgG fusions and SPR detection were used in these experiments. Subsequent reporter cell-based assays showed that Arg143 (end of the NKp30 stalk region) alignment with the aspartate of CD3ζ is required for signal transduction and that this alignment might be achieved by ligand-induced receptor clustering and/or stalk-dependent conformational changes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impaired oligomerization would then translate into lower apparent binding affinities, when using surface-based methods such as SPR and ELISA, and into impaired signal transduction in cell-based experiments. The role of the stalk domain in CD3ζ-mediated activation of NK cells was thoroughly characterized by Memmer et al [ 7 ] who showed that mutations in the stalk region close to LBD weaken the K D of B7-H6-Fc whereas BAG-6 binding, again, remained mostly unaffected, although NKp30-Fc IgG fusions and SPR detection were used in these experiments. Subsequent reporter cell-based assays showed that Arg143 (end of the NKp30 stalk region) alignment with the aspartate of CD3ζ is required for signal transduction and that this alignment might be achieved by ligand-induced receptor clustering and/or stalk-dependent conformational changes [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such an arrangement would bring the membranes of both cells into very close contact, and such an effect could be further potentiated by NKp30 oligomerization. Local deformation of the NK cell plasma membrane caused by the conformational change of the stalk region induced by ligand binding might trigger signal transduction through the CD3ζ chains associated with the NKp30 transmembrane domain thanks to the interaction of CD3ζ Asp36 residue with NKp30 Arg143 residue occurring at plasma membrane which is required for NKp30 signaling [ 7 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Ligand binding and signaling function by NKp30 is highly dependent upon integrity of the membrane proximal stalk region (35). Crystal structures have revealed that NKp30 and NKp44 can form homodimeric structures with NKp30 dimerizing in a head-to-tail fashion to form an I-type Ig-like fold and two NKp44 V-type Ig-like domains form a saddle-shaped dimer with unique disulfide bridging (36, 37).…”
Section: Ncrs and Their Structuresmentioning
confidence: 99%
“…One particular work demonstrated that, upon binding of B7‐H6, conformational changes in NKp30 enable the translocation of Arg143 to a position deeper in the phospholipid bilayer. As a result, the positively charged arginine residue aligns with the negatively charged aspartate in CD3ζ or FCεRIγ adaptor proteins, which triggers the NK cell response (Memmer et al, 2016).…”
Section: Nkp30 As a Mediator Of Nk Activitymentioning
confidence: 99%